Preparation of Andrographis Paniculata and Rosa Formulation and its Antibacterial Activity Against Urinary Tract Infection Causing Pathogens - Thiraviarajan Akash; Shanmugam Rajeshkumar; Munusamy Tharani (Wolters Kluwer Medknow Publications, 2024)
Andrographis Paniculata also known as the "King of Bitters" is a herbal medicine of the Acanthaceae family which is native to India and Sri Lanka. Andrographis Paniculata is a very useful medicinal plant as it has antioxidant, antidiabetic, antipyretic, anticancer properties. The main antibacterial activity of Andrographis Paniculata is due to the presence of andrographolide and arabinogalactan proteins. The medicinal properties of rose are mostly due to their abundance in phenolic compounds. They have many pharmacological properties like antibacterial, antioxidant, thrombolytic, and anticancer properties. The hips of the rose plant have Vitamin C in a concentration that is three times more than a citrus fruit that can be used in the treatment of a flu or a cold. Mueller-Hinton agar was utilized for this activity to determine the zone of inhibition. The plant extracts with different concentrations were loaded, and the plates were incubated for 24 hours at 37°C. After the incubation time, the zone of inhibition was measured. The results of this study are significant because they demonstrate the antibacterial activity of Andrographis Paniculata and Rosa against three bacterial pathogens. This suggests that the formulation of Andrographis Paniculata and Rosa has potential as a natural antibacterial agent. Further studies are needed to explore the mechanism of action and potential applications of this formulation. In conclusion, the study shows that the formulation of Andrographis Paniculata and Rosa has significant antibacterial activity against Klebsiella, Escherichia Coli, and Enterococcus Faecalis. This suggests that the formulation of Andrographis Paniculata and Rosa has potential as a natural antibacterial agent that could be further explored for its potential use in the treatment of bacterial infections.